2014
DOI: 10.1088/1475-7516/2014/06/061
|View full text |Cite
|
Sign up to set email alerts
|

Ruling out the power-law form of the scalar primordial spectrum

Abstract: Abstract. Combining Planck CMB temperature [1] and BICEP2 B-mode polarization data [2,3] we show qualitatively that, assuming inflationary consistency relation, the power-law form of the scalar primordial spectrum is ruled out at more than 3σ CL. This is an important finding, since the power-law form of the scalar primordial spectrum is one of the main assumptions of concordance model of cosmology and also a direct prediction of many inflationary scenarios. We show that a break or step in the form of the primo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 70 publications
2
39
0
Order By: Relevance
“…There was in fact even some indication of a preference over a power-law spectrum [512][513][514][515][516]. However, this conclusion had to be revised after the re-evaluation of the BICEP2 data using additional information from Planck and the Keck array [517] which showed that the B-mode signal originally attributed to primordial tensor perturbations can be explained in terms of polarised galactic dust emission.…”
Section: Models With a Large Scale Power Suppressionmentioning
confidence: 99%
“…There was in fact even some indication of a preference over a power-law spectrum [512][513][514][515][516]. However, this conclusion had to be revised after the re-evaluation of the BICEP2 data using additional information from Planck and the Keck array [517] which showed that the B-mode signal originally attributed to primordial tensor perturbations can be explained in terms of polarised galactic dust emission.…”
Section: Models With a Large Scale Power Suppressionmentioning
confidence: 99%
“…The WWI model was introduced in [16] in order to address two major issues. Firstly with the BICEP2 B-mode signal, assuming to be primordial, we ruled out the power law form of scalar power spectrum with more than 3σ confidence [13]. We needed a strong suppression of scalar power at large scales and at the same time large tensors with low non-Gaussianities.…”
Section: Wiggly Whipped Inflationary Scenariomentioning
confidence: 99%
“…Moreover, as we have just discussed, the running of the scalar power spectrum cannot be used within slow-roll inflation to alleviate the above-mentioned tension, precisely because it cannot take large enough values. Solely in slow-roll violating models of inflation, such an explanation may be relevant [137][138][139][140][141].…”
Section: From This Equation One Hasmentioning
confidence: 99%